1996
DOI: 10.1074/jbc.271.12.7104
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific Versus Isoform-specific Differences in Cation Activation Kinetics of the Na,K-ATPase

Abstract: The experiments described in this report reconcile some of the apparent differences in isoform-specific kinetics of the Na,K-ATPase reported in earlier studies. Thus, tissue-specific differences in Na+ and K+ activation kinetics of Na,K-ATPase activity of the same species (rat) were observed when the same isoform was assayed in different tissues or cells. In the case of alpha1, alpha1-transfected HeLa cell, rat kidney, and axolemma membranes were compared. For alpha3, the ouabain-insensitive alpha3*-transfecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
68
2
10

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 46 publications
4
68
2
10
Order By: Relevance
“…In cultured rat astrocytes, 0.1-1.0 M of ouabain inhibits the Na ϩ pump (29) and increases stored Ca 2ϩ (V. Golovina and M.P.B., unpublished work). These ouabain concentrations are at least 100-fold below the IC 50 for inhibition of rat ␣1 (1,6,29,30). Thus, we infer that the PM must contain functional ␣2 (astrocytes) or ␣3 (myocytes) subunits.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…In cultured rat astrocytes, 0.1-1.0 M of ouabain inhibits the Na ϩ pump (29) and increases stored Ca 2ϩ (V. Golovina and M.P.B., unpublished work). These ouabain concentrations are at least 100-fold below the IC 50 for inhibition of rat ␣1 (1,6,29,30). Thus, we infer that the PM must contain functional ␣2 (astrocytes) or ␣3 (myocytes) subunits.…”
Section: Resultsmentioning
confidence: 80%
“…The catalytic ␣ subunit of this transport protein contains the binding site for the selective Na ϩ pump inhibitor, ouabain (1,2). Isoforms of the ␣ subunit with high affinity (␣2 and ␣3) and low affinity (␣1) for ouabain have been characterized; indeed, the ouabain affinities differ greatly in a few species, including the rat (1,2), where the IC 50 is Ͼ10,000 nM for ␣1, and only 10-500 nM for ␣2 and ␣3 (1,6). These isoforms also exhibit kinetic (ion affinity) differences (1,2,7).…”
mentioning
confidence: 99%
“…The Na pump's functional properties are known to vary depending on the particular subunit combination of its isoforms, as well as the cellular͞tissue environment in which these combinations are located (2)(3)(4)(5)(6). In addition, there are also variations in the pump's isoform composition that differ in their tissue͞ species distribution and in their developmental stage (2)(3)(4).…”
mentioning
confidence: 99%
“…If the abundance of reticulocyte mRNA is a measure of the abundance of protein in the mature red cell (most of the copies of Na,K-ATPase contain the ␣1 isoform of the ␣ subunit, and few contain the ␣3 isoform), then the complexation of ␣1 with either ␤2 or ␤3 should govern most of the kinetics, implying that complexes containing ␣3 should have a minor influence. Most studies link the catalytic activity overwhelmingly to the ␣ subunit, and studies of different combinations of ␣ and ␤ subunits (9)(10)(11)(12) have not yet shown any dramatic differences in their kinetic characteristics. However, in none of the aforementioned studies was uncoupled sodium efflux investigated.…”
Section: Discussionmentioning
confidence: 99%
“…␤3 was recently found in human placenta and various rat tissues (6). Although ␣ is the catalytically important subunit (7,8), kinetic studies of combinations of ␣1, ␣2, and ␣3 with ␤1 and ␤2 (9)(10)(11)(12) indicated that the kinetic parameters of the Na,K-ATPase can be influenced by different combinations of isoforms of the ␣ and ␤ subunits. However, uncoupled sodium efflux was not investigated in any of these studies.…”
mentioning
confidence: 99%